2017
DOI: 10.1038/gim.2016.221
|View full text |Cite
|
Sign up to set email alerts
|

Prospective comparison of the cost-effectiveness of clinical whole-exome sequencing with that of usual care overwhelmingly supports early use and reimbursement

Abstract: Use of WES early in the diagnostic pathway more than triples the diagnostic rate for one-third the cost per diagnosis, providing strong support for reimbursement as a clinical test.Genet Med advance online publication 26 January 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
211
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 204 publications
(230 citation statements)
references
References 20 publications
7
211
0
2
Order By: Relevance
“…After titles and abstracts were screened and full-text publications assessed for eligibility, 14 publications were identified that fulfilled the inclusion criteria. A review of the reference lists of retrieved publications and the publications of recognized authors in this field identified 22 additional relevant publications (7 of which were identified after July 2016, the planned end date for literature screening [18][19][20][21] ). Overall, 36 relevant publications were identified.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…After titles and abstracts were screened and full-text publications assessed for eligibility, 14 publications were identified that fulfilled the inclusion criteria. A review of the reference lists of retrieved publications and the publications of recognized authors in this field identified 22 additional relevant publications (7 of which were identified after July 2016, the planned end date for literature screening [18][19][20][21] ). Overall, 36 relevant publications were identified.…”
Section: Resultsmentioning
confidence: 99%
“…5,6,[8][9][10][46][47][48] Of the eight full economic evaluations, two were CUAs 22,23 and six were CEAs, published between 2014 and 2017 in Australia (2), the United States (1), the UK (1), the Netherlands (1), and Canada (1). [18][19][20][21][28][29][30] Of these publications, the study by Soden et al 29 did not directly report WES costs but estimated Population unclear 2 (6) No study population 6 (17) WES, whole-exome sequencing; WGS, whole-genome sequencing. a Two costutility analyses, six cost-effectiveness analyses.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Australian Genomics has published health economic data demonstrating the value for childhood syndrome patients seen at the Royal Children's Hospital of Melbourne, where the use of whole-exome sequencing increased the diagnostic rate 5-fold over traditional diagnostic tests while decreasing the average cost per patient by 75% [9]. Additionally, 4 times more patients saw improvements in their medical care.…”
Section: Genome Sequencing In Healthcarementioning
confidence: 99%